Stabilized open metal sites in bimetallic metal–organic framework catalysts for hydrogen production from alcohols. Issue 17 (22nd April 2021) - Snider, Jonathan L.; Su, Ji; Verma, Pragya; El Gabaly, Farid; Sugar, Joshua D.; Chen, Luning; Chames, Jeffery M.; Talin, A. Alec; Dun, Chaochao; Urban, Jeffrey J.; Stavila, Vitalie; Prendergast, David; et al.
Abstract : Bimetallic (Ni x Mg1− x )-MOF-74 stabilizes Ni 2+ open metal site relative to Ni-MOF-74, resulting in a highly active and selective alcohol dehydrogenation catalyst. Abstract : Liquid organic hydrogen carriers such as alcohols and polyols are a high-capacity means of transporting and reversibly storing hydrogen that demands effective catalysts to drive the (de)hydrogenation reactions under mild conditions. We employed a combined theory/experiment approach to develop MOF-74 catalysts for alcohol dehydrogenation and examine the performance of the open metal sites (OMS), which have properties analogous to the active sites in high-performance single-site catalysts and homogeneous catalysts. Methanol dehydrogenation was used as a model reaction system for assessing the performance of five monometallic M-MOF-74 variants (M = Co, Cu, Mg, Mn, Ni). Co-MOF-74 and Ni-MOF-74 give the highest H2 productivity. However, Ni-MOF-74 is unstable under reaction conditions and forms metallic nickel particles. To improve catalyst activity and stability, bimetallic (Ni x Mg1− x )-MOF-74 catalysts were developed that stabilize the Ni OMS and promote the dehydrogenation reaction. An optimal composition exists at (Ni0.32 Mg0.68 )-MOF-74 that gives the greatest H2 productivity, up to 203 mL gcat −1 min −1 at 300 °C, and maintains 100% selectivity to CO and H2 between 225–275 °C. The optimized catalyst is also active for the dehydrogenation of other alcohols. DFT calculations reveal that synergistic interactions between the open metal site and the organic linker lead to lower reaction barriers in the MOF catalysts compared to the open metal site alone. This work expands the suite of hydrogen-related reactions catalyzed by MOF-74 which includes recent work on hydroformulation and our earlier reports of aryl-ether hydrogenolysis. Moreover, it highlights the use of bimetallic frameworks as an effective strategy for stabilizing a high density of catalytically active open metal sites.